Preparation method of low-digestibility starch-theanine-EGCG (epigallocatechin gallate) ternary complex
Ultrasonic treatment of the mixture of starch, theanine and EGCG is used to form a low digestible complex, which solves the problem of excessive starch digestion rate and achieves the effect of delaying blood sugar rise and improving the stability of the complex.
Patent Information
- Application Number
- CN202510039570.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively reduce the digestion rate of starch, resulting in fluctuations in postprandial blood sugar levels and increasing the risk of diabetes and related complications.
The starch, theanine and EGCG were mixed and sonicated, a low digestible starch-theanine-EGCG ternary complex was formed. The method includes dispersing the starch in water and adding theanine and EGCG, sonication for 10-45 minutes, followed by lyophilization.
It significantly reduces the digestion rate of starch, delays blood sugar rise, has potential preventive and auxiliary treatment of metabolic diseases, and improves the stability and functionality of the complex.
Smart Images

Figure CN119817738A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a low digestible starch-theanine-EGCG ternary complex, belonging to the technical field of functional foods. Background Art
[0002] As we all know, starch is widely distributed in nature and is the main form of carbohydrates in plants. Starch from different plant sources has different granule shapes and sizes. In addition, as the main energy substance in human dietary intake, starch also has the function of providing heat energy and improving food texture. After digestion and metabolism by the human body, it plays a very important role in blood sugar response. The starch digestion process involves the catalytic action of enzymes to break down complex carbohydrates into absorbable glucose units. Digestion efficiency directly affects the nutritional value of food and the blood sugar level of the human body. However, excessive postprandial blood sugar concentration (especially the intake of starchy foods) is the main factor leading to type 2 diabetes and related complications. In the context of people's increasing attention to food nutrition and health, the development of starchy foods that digest slowly has become a hot research direction.
[0003] Tea is one of the most popular beverages in the world. Green tea contains a variety of active ingredients, among which L-theanine (THE) and epigallocatechin gallate (EGCG) are the main active ingredients of green tea, which have multiple physiological activities such as antioxidant, anti-inflammatory and cardiovascular health promotion. In the food industry, THE and EGCG are often added to starch-based foods to improve their nutritional value and functional properties. Previous studies have reported that THE can bind to starch molecules through non-covalent interactions such as hydrogen bonds in an ultrasonic field, thereby significantly increasing the resistant starch content in THE-modified starch by 7.69% and inhibiting short-term blood sugar elevation. However, there are few studies on the joint effects of endogenous substances (THE and EGCG) in tea leaves on starch structure and digestibility. In addition, ultrasonic treatment (UC) as a physical modification method has attracted much attention in the field of food science in recent years. Through the cavitation effect generated by sound waves, UC can significantly change the physicochemical properties of starch, thereby improving its functional properties. At the same time, it can also change the crystal structure and surface properties of starch granules, resulting in an increase in the apparent content of starch. In addition, after UC, the reaction efficiency between the host molecule and the guest molecule is improved, and the interaction with other compounds is also enhanced. Based on the above studies, we speculate that UC can promote the interaction between THE / EGCG and MS to form a stable complex. At present, there is still limited research on the effect of UC on the formation of MS-THE / EGCG complex, which may exhibit unique physicochemical properties during food processing and storage. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a low digestible starch-theanine-EGCG ternary complex.
[0005] To achieve the above-mentioned purpose and other related purposes, the technical solution provided by the present invention is: a method for preparing a low digestible starch-theanine-EGCG ternary complex, comprising the following steps:
[0006] Step 1: Dispersing starch in water, adding theanine and epigallocatechin gallate to obtain a mixed solution;
[0007] Step 2: subjecting the mixed solution to ultrasonic treatment for 10-45 minutes at a temperature of 10-15°C;
[0008] Step 3: After freeze drying, the starch-theanine-EGCG ternary complex is obtained.
[0009] The preferred technical solution is: the amount of theanine is 5-15% of the dry weight of starch; the amount of epigallocatechin gallate is 3-8% of the dry weight of starch.
[0010] The preferred technical solution is: the process parameters of the ultrasonic treatment are: the frequency of the ultrasonic treatment is 300W, set to turn on for 5 seconds and turn off for 5 seconds.
[0011] The preferred technical solution is: the starch is straight-chain starch.
[0012] The preferred technical solution is: the starch is corn starch.
[0013] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0014] 1. Significantly improved the digestion characteristics of starch: Through the synergistic effect of theanine and EGCG, combined with ultrasonic treatment technology, the present invention can effectively reduce the digestion rate of starch and significantly increase the content of resistant starch, thereby achieving the effect of delaying the rise of blood sugar, and has the potential to prevent and assist in the treatment of metabolic diseases (such as diabetes and obesity).
[0015] 2. Improved stability and functionality of the composite: The use of optimized ultrasonic treatment parameters (such as treatment time, frequency and temperature) can significantly enhance the crystal structure of the composite, so that the composite exhibits higher physical and chemical stability during storage and use, thereby extending the shelf life of the product.
[0016] 3. Simple and efficient preparation process: Compared with the existing complex physical or chemical modification methods, the process route of ultrasonic treatment and freeze-drying adopted in the present invention is not only simple to operate and low in cost, but also avoids the use of chemical reagents, thus meeting the requirements of green environmental protection.
[0017] 4. Diversified functions of the complex: Since both theanine and EGCG have antioxidant, anti-inflammatory and blood sugar regulating effects, the ternary complex of the present invention can not only regulate starch digestion, but also provide additional health benefits through its active ingredients, and is suitable for the field of functional foods and nutritional supplements.
[0018] 5. Wide application scope: The preparation method of the present invention is applicable to various types of starch, especially starch with a high straight chain content, because it has broad application prospects in the fields of food industry, medicine, etc., which enhances the versatility and market value of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Effect of ultrasound on the digestibility curve (A) and relative starch content (B) of MS-THE / EGCG complex.
[0020] Figure 2 Effect of ultrasonic treatment on the scanning electron microscopy image (5000×) of MS-THE / EGCG complex.
[0021] Figure 3 Effects of ultrasonic treatment on the adhesion behavior curve (A), apparent viscosity (B), storage modulus (C), loss modulus (D), X-ray diffraction pattern (E) and infrared spectrum (F) of MS-THE / EGCG composites.
[0022] Figure 4 Ultrasonic treatment on the deconvolution of infrared spectra of MS-THE / EGCG complex (A, B), Raman spectra (C), 13 Effect of CNMR CP / MAS spectra (D), DSC curves (E) and thermal enthalpy (F). DETAILED DESCRIPTION
[0023] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in the embodiments.
[0024] See also Figure 1-4 It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with the technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention. Therefore, they have no technical substantive significance. Any modification of the structure, change of the proportion relationship or adjustment of the size. The following examples are provided for a better understanding of the present invention, but are not intended to limit the present invention.
[0025] Corn starch and L-theanine (purity ≥ 98%) were produced by Aladdin Co., Ltd. (Shanghai, China), and epigallocatechin gallate (purity ≥ 98%) was produced by Huzhou Rongkai Plant Extract Co., Ltd.
[0026] Unless otherwise specified, the reagents or materials described in the following examples are commercially available.
[0027] The technical solution of the present invention is further described in detail below with reference to examples.
[0028] Example: A low digestible starch-theanine-EGCG ternary complex prepared by ultrasound control and its preparation method
[0029] An ultrasonically regulated starch-theanine-EGCG ternary complex and a preparation method thereof, wherein the preparation method comprises the following steps:
[0030] Weigh 15 g of corn starch into a beaker, add 100 mL of deionized water, then add 10% THE and 5% EGCG (based on dry starch), and mix thoroughly for 40 minutes. The mixture was treated with an ultrasonic homogenizer (JY92-IIDN; Ningbo Sante Biotechnology Co., Ltd., Ningbo, China). The power was set to 300 W (on 5 seconds, off 5 seconds), and the treatment time was set to 15, 30, and 45 minutes, respectively. To prevent the temperature from rising too high, the treatment process was carried out in an ice water bath. After that, the mixture was stirred at room temperature for 2 hours and then centrifuged at 5,000 g for 15 minutes to obtain a precipitate. After freeze-drying, the precipitate was named "MS-THE / EGCG-U X ”, where “X” represents the processing time.
[0031] Note: In this application, MS stands for "corn starch", THE stands for "theanine", and EGCG stands for "epigallocatechin gallate".
[0032] Performance data
[0033] 1. Determination of in vitro digestibility
[0034] 1.1. Content of various starch components
[0035] The RDS, SDS and RS contents in starch were determined according to the method of Englyst et al. with slight modifications. In brief, 0.2 g (dry basis) of starch sample was placed in a conical flask, 20 mL of 0.1 M buffer (pH 5.2) was added, and heated at 95°C for 30 minutes. The mixture was then cooled to about 37°C, 5 mL of enzyme solution (α-amylase: 12 U / mg, glucosidase: 260 U / mL) was added, and placed in a water bath oscillator (37°C, 170 rpm). After 20 minutes, 0.5 mL of the mixed solution was added to 20 mL of 70% ethanol and centrifuged for 5 minutes (4000 r / min). 0.1 mL of the supernatant was added to 3 mL of GOPOD solution (Nanjing Jiancheng Bioengineering Institute) and incubated in a 37°C water bath for 10 minutes. Finally, the absorbance was measured at a wavelength of 505 nm. After 120 minutes, the absorbance of the sample was measured using the same method as above. The calculation method is as follows
[0036] RDS(%)=[(G 20 -G0)x0.9] / TSx 100
[0037] SDS(%)=[(G 120 -G 20 )x0.9] / TSx 100
[0038] RS(%)=(1-RDS-SDS)x100
[0039] Where G0 represents the amount of glucose before hydrolysis; G 20 Indicates the amount of glucose released within 20 minutes of hydrolysis; G 120 It indicates the amount of glucose released within 120 min of hydrolysis; TS indicates the mass of total starch dry basis (mg).
[0040] The digestibility of native MS and ultrasound-modified complex (MS-THE / EGCG) and the extent of hydrolysis at different times were determined by simulated in vitro method. Figure 1 In the hydrolysis curve, each sample hydrolyzed rapidly within 10-60 minutes and then gradually stabilized. 30The hydrolysis curve of was the lowest, indicating that it had the strongest resistance to hydrolysis. Correspondingly, the contents of RDS, SDS and RS were 62.53%, 3.18% and 34.29%, respectively. During ultrasonic treatment, the addition of THE and EGCG significantly reduced the digestibility of MS, while increasing the content of resistant starch. The cavitation effect of ultrasound produced strong physical and mechanical effects in the liquid, including the formation of local high pressure. This environmental condition helps to enhance the interaction between THE and EGCG and starch molecules and form a stable composite structure. Specifically, ultrasound accelerates the collision frequency and binding rate of THE and EGCG molecules with starch molecules by increasing bubbles and local turbulence in the solution. These interactions may involve hydrogen bonds, hydrophobic interactions, and van der Waals forces that promote the formation of complexes. In this case, it is believed that THE and EGCG may form a protective layer or slow down the enzymatic hydrolysis of starch by binding to starch, thereby regulating the digestion kinetics of starch.
[0041] 2. Microstructure observation
[0042] The microstructure of each sample was photographed using a scanning electron microscope. Prior to this, each sample was mounted on a conductive glue and coated with gold for 30 seconds, and then observed at a specific magnification at an accelerating voltage of 3 kV.
[0043] The effect of ultrasonic treatment on the scanning electron microscopy images of MS-THE / EGCG complex is shown in the attached Figure 2 .
[0044] In SEM analysis, we observed and compared the MS-THE / EGCG complexes with different sonications ( Figure 2 ). Compared with the polyhedral shape and smooth surface of natural MS, the surface of the MS-THE / EGCG composite showed a uniform and compact structure, and starch granules were uniformly mixed with THE and EGCG under appropriate ultrasound. Here, THE and EGCG may bind to the interior or surface of starch through non-covalent interactions and may form a protective layer, which allows MS to agglomerate and adhere. However, as the ultrasound time increases, we observed that the composite structure gradually became irregular and uneven. Too long processing time may cause the microstructure of the starch granule surface to be destroyed, manifested as granule dissolution, irregular morphology, and even partial gelatinization. Therefore, the results of SEM analysis indicate that appropriate ultrasound can improve the structure of the MS-THE / EGCGG composite to a certain extent, but too long processing time may cause irreversible changes in the starch structure and make the composite unstable.
[0045] 3. Determination of gelatinization performance
[0046] Accurately weigh 3g of the prepared sample in an aluminum can, add 25mL of deionized water, and stir evenly. Use a rapid viscosity analyzer to test according to standard 1 method. The test results are shown in Table 1 and Figure 3 A.
[0047] Table 1 Effect of ultrasonic treatment on the adhesive properties of MS-THE / EGCG composites
[0048]
[0049]
[0050] Data are presented as mean ± SD of triplicates. Different superscript letters in the same column indicate significant differences (p < 0.05).
[0051] Figure 3 A shows the pasting properties of the MS-THE / EGCG composites treated with ultrasound, and the specific pasting parameters are listed in Table 1. The pasting properties of MS are similar to those of previous studies. Among them, the retrogradation value is 1158.00 cP, which is because the higher content of amylose in MS compared with other starches makes MS prone to aging. After the addition of THE and EGCG, the gelatinization parameters of each sample increased significantly (p<0.05). In particular, after ultrasound, the viscosity of the MS composite system will increase further. Ultrasonic treatment can release energy through the high-pressure area generated by fluctuations and micro-bubble collapse, thereby enhancing the interaction between MS and THE / EGCG molecules. At the same time, it may also induce conformational changes in THE and EGCG molecules. These structural reorganizations and densifications make the molecular structure within the composite more ordered and compact, increasing the intermolecular interaction force. In other words, within the 30-min treatment time, the main function of ultrasound is to accelerate the binding of guest molecules to MS and increase the viscosity of this composite system. The above research results indicate that appropriate ultrasonic treatment can improve the peak viscosity and stability of the MS-THE / EGCG complex, which may lay the foundation for improving the anti-enzyme properties of the complex system.
[0052] 4. Rheological properties
[0053] The gelatinized samples were subjected to rheological analysis using a rheometer with a parallel plate diameter of 40 mm. First, the temperature of the parallel plate was set to 25°C, and G′ and G″ were recorded at 0.1-100 rad / s (0.1% in the linear viscoelastic region). Then, the temperature of the parallel plate was set to 25°C, and the G′ and G″ were recorded at 0.1-100 rad / s (0.1% in the linear viscoelastic region). -1 The viscosity was tested at a shear rate of .
[0054] The test results are attached. Figure 3 BD.
[0055] In the shear rate range of 0.1-100l / s, the viscosity of the sample shows a downward trend due to the shear thinning effect. This phenomenon is usually due to the tendency of the polymer or molecular chains in the gel to stretch and rearrange under shear. This stretching and rearrangement leads to a reduction in the cross-linking between molecular chains, thereby weakening the three-dimensional network structure of the gel and causing a decrease in the overall viscosity. MS-THE / EGCG-U 30 It showed higher viscosity, showing improved consistency and shear thinning properties after ultrasound. This may be due to the addition of THE and EGCG, especially the hydroxyl groups in EGCG, which can compete with starch for the binding of water molecules, weaken the interaction with water molecules, and promote the entanglement and aggregation between starch chains. Subsequently, the viscosity of the complex (45 minutes) showed a downward trend. This may be due to the fact that UC dominated for a long time, dissolving part of the starch (mainly amylose), allowing THE and EGCG to bind to more starch molecules, thereby inhibiting the interaction between molecular chains, and ultimately leading to the destructive effect of decreasing the overall viscosity of the complex system. In terms of dynamic rheology, Figure 3 The CD shows that with the change of frequency (0.1-100rad / s), the storage modulus (G′) of each sample is significantly greater than the loss modulus (G″). This indicates that the composite system is a typical weak gel dynamic rheological system. The G′ and G″ of the composite system increase with the extension of ultrasonic treatment time and are higher than MS. Ultrasonic treatment promotes the formation of weak gel by enhancing the interaction between starch, THE and EGCG in the mixture. This is consistent with the results of static rheology, indicating that appropriate ultrasound can further enhance the stability and structure of the gel.
[0056] 5. X-ray diffraction analysis (XRD)
[0057] XRD patterns of all samples were obtained using XRD at 40 kV and 100 mA. All samples were measured from 5° to 40° at a speed of 5° / min.
[0058] The test results are attached. Figure 3 E.
[0059] MS exhibited typical type A crystal characteristics. The addition of ultrasonic treatment or THE / EGCG only changed the intensity of the diffraction peak, but the crystalline shape of MS did not change. When THE and EGCG were used in combination with MS, the relative crystallinity decreased significantly (from 36.61% to 20.30%). This is mainly due to the fact that they are bound to each other in non-covalent forms such as hydrogen bonds or hydrophobic interactions, which greatly weakened the crystalline structure of MS. At the same time, with the increase of ultrasonic time, the crystallinity of the MS-THE / EGCG complex increased by 10.52%, but the MS-THE / EGCG-U 45The crystallinity of the MS-THE-EGCG complex decreased to 20.77%, indicating that the ultrasonic treatment within a limited time promoted the densification of the complex architecture. We speculate that ultrasound can effectively promote the rearrangement and assembly of starch, THE, and EGCG molecules through the shear force induced in the liquid and the local high-pressure area, during which the double helical structure of starch granules is opened and more hydroxyl groups are exposed. This effect in the complex system may contribute to the reformation of the crystalline structure, especially in the early stage of ultrasonic treatment (<30 minutes), when the strong field of ultrasonic treatment helps to form a more ordered and stable MS-THE-EGCG complex. However, extending the ultrasonic treatment time showed the opposite trend, mainly because the extended treatment time leads to the depolymerization of amylose, thereby destroying the weak hydrogen bonds formed by THE and EGCG with MS molecules.
[0060] 6. Infrared spectroscopy and Raman spectroscopy
[0061] The dried sample was mixed with KBr at a ratio of 1:100, ground and pressed into tablets, and the spectra were recorded using a Fourier transform infrared spectrometer. The spectral scanning range was 4000-400 cm -1 , resolution 4cm -1 The deconvoluted spectra were calculated using Omnic software for 1047 / 1022 and 1022 / 995 cm -1 In addition, to further determine the short-range order, Raman spectroscopy was used to measure the 480 cm -1 In addition, the test range is 3200-100cm -1 , the laser source is 785nm.
[0062] The test results are attached. Figure 3 F and Figure 4 AC.
[0063] Figure 3 F represents the Fourier transform infrared spectra of MS-THE / EGCG complex and MS. Compared with the experimental group, the 3407cm -1 The broad peaks at 292, 930, 1023, and 1081 cm are the stretching vibrations of the intermolecular hydroxyl group (-OH). -1 The peaks at 3700-3100 cm represent the asymmetric absorption peak of -CH2- and the vibration contraction absorption peak of COH. -1 The width of the peak formed at is obviously gradually increased, and no new peaks are generated in the single spectrum, which indicates that MS and THE / EGCG form a complex through non-covalent interactions mainly through hydrogen bonds. Figure 4In AB, for MS-THE / EGCG complex, when the ultrasonic time was within 0-30 min, R 1047 / 1022 The value increased from 0.817 to 0.928, R 1022 / 995 It dropped to 0.774. Then, R 1047 / 1022 The value decreased significantly (p<0.05), indicating that the order of the MS-THE / EGCG complex was destroyed. In order to further verify the short-range order of the MS-THE / EGCG complex, we performed Raman spectroscopy tests on the samples. The results are as follows Figure 4 As shown in C. Similar to the trend of Fourier transform infrared spectroscopy, the FWHM used to characterize the short-range order of the sample decreased from 17.42 to 15.47, and then increased significantly. These changes can be explained by the physical changes caused by ultrasound in the structure of the MS-THE / EGCG complex. In the early stage of treatment, ultrasound can promote the interaction between starch molecules and THE / EGCG and enhance the short-range order. However, as the treatment time increases, the order of the internal structure of the MS-THE / EGCG complex begins to be destroyed or disintegrated. Ultrasound triggers changes in the arrangement of starch molecules or changes in the interaction between THE / EGCG molecules.
[0064] 7. 13 C CP / MAS Nuclear Magnetic Resonance (NMR) Spectroscopy
[0065] About 100 mg of sample was placed in a rotating cylinder with a diameter of 4 mm and recorded with a Bruker AV400 spectrometer. The number of scans was 3000 with a cycle interval of 2 seconds.
[0066] The test results are attached. Figure 4 D.
[0067] The tightness of the helical structure of the starch complex has a great influence on digestibility. Figure 4 D shows the sample 13CNMR spectrum, including C1 region, C2, 3 and 5 regions, C4 region and C6 region. C1 region is between 100-110ppm and is very sensitive to changes in starch crystal type. When starch is composed of three glucose residues arranged in a spiral symmetric manner, a triplet peak appears in C1 region, indicating that the starch is type A crystal. After ultrasound, the crystal type of MS-THE / EGCG complex did not change. However, when ultrasound was continued (>30 minutes), the triplet peak of the complex system gradually disappeared, indicating that long-term or high-power ultrasound would make the crystal characteristics of starch complexes less obvious. After ultrasound treatment (0-30 minutes), the single helical structure content of MS-THE / EGCG complex increased significantly (p<0.05), which may be due to the fact that ultrasound treatment increases the mobility of linear starch molecules, and some linear molecules rotate to form new single helical structures. Another explanation is that part of EGCG may enter the starch cavity and form a new single helical structure. However, due to the local thermal effect, long-term ultrasound leads to starch gelatinization, which in turn leads to a decrease in single helical and double helical content and an increase in amorphous content.
[0068] 8. Differential Scanning Calorimetry
[0069] Thermodynamic properties were determined by DSC. Briefly, 3.0 mg of sample was accurately weighed in an aluminum crucible, 3 times the mass of deionized water was added, sealed, and then equilibrated at 4 °C for 24 hours. The heat change was scanned in the range of 30-130 °C at a rate of 10 °C / min, and the DSC changes and thermal parameters during the process were recorded, including the onset temperature (T o ), peak temperature (T p ), termination temperature (T c ) and enthalpy (ΔH).
[0070] The test results are attached. Figure 4 EF.
[0071] Figure 4 The E shows the thermal properties of MS and MS-THE / EGCG composites. Generally speaking, this is because the ultrasonic force destroys the starch structure, accelerates the entry of water into the granules, and promotes the gelatinization of starch, which also leads to a decrease in ΔH ( Figure 4F). For ΔH, it is inseparable from crystallinity, amylose, amylopectin, ordered structure, etc. Initially, the ΔH of the MS-THE / EGCG complex increased from 7.40 J / g to 9.30 J / g at a shorter ultrasonic time, and then decreased significantly at 45 min (p<0.05). Based on the above facts, this indicates that appropriate ultrasonic treatment promotes the formation of ternary complexes because it can produce ultrasonic cavitation effects, accelerate the rearrangement between ternary complexes through hydrogen bonds, and thus form a more ordered structure and higher relative crystallinity. On the other hand, ultrasound mainly focuses on destroying the amorphous region more obviously, in which case the remaining crystalline structure may have better stacking. However, the structure of MS particles is gradually destroyed in the continuous time treatment. In addition, the local temperature rise induced by ultrasound can lead to starch depolymerization and degradation, especially amylose. Although THE and EGCG form complexes on starch molecules, a large number of water molecules are more likely to enter the interior of starch granules at this time, resulting in a decrease in ΔH and reduced thermal stability.
[0072] The above description is only used to explain the preferred embodiments of the present invention, and is not intended to limit the present invention in any form. Therefore, any modifications or changes made to the present invention under the same inventive spirit should still be included in the scope of protection intended by the present invention.
Claims
1. A method for preparing a low digestible starch-theanine-EGCG ternary complex, characterized in that: The following steps are involved: Step 1: Dispersing starch in water, adding theanine and epigallocatechin gallate to obtain a mixed solution; Step 2: subjecting the mixed solution to ultrasonic treatment for 10-45 minutes at a temperature of 10-15°C; Step 3: After freeze drying, the starch-theanine-EGCG ternary complex is obtained.
2. The method for preparing the low digestible starch-theanine-EGCG ternary complex according to claim 1, characterized in that: The amount of theanine used is 5-15% of the dry weight of starch; the amount of epigallocatechin gallate used is 3-8% of the dry weight of starch.
3. The method for preparing the low digestible starch-theanine-EGCG ternary complex according to claim 1, characterized in that: The process parameters of ultrasonic treatment are as follows: the frequency of ultrasonic treatment is 300W, set to on for 5 seconds and off for 5 seconds.
4. The method for preparing the low digestible starch-theanine-EGCG ternary complex according to claim 1, characterized in that: The starch is amylose.
5. The method for preparing the low digestible starch-theanine-EGCG ternary complex according to claim 4, characterized in that: The starch is corn starch.